First Steps Of Steppe Eagle Conservation In Central Kostanay Oblast Using Artificial Nests (Republic Of Kazakhstan) - Rishat R. Batryakov (Пернатые хищники и их охрана)
The Steppe Eagle (Aquila nipalensis) nests across a great swath of Kostanay Oblast. The greatest number and density of nesting pairs is concentrated in to the south. Northernmost nesting points are located in Kamysty, Auliekol and Nauru districts, located centrally in the oblast